IMPLEMENTATION BINARY LOGISTIC MODEL ON FACTORS AFFECTING A PERSON'S SMOKING STATUS - Yunita Yunita; Pardomuan Robinson Sihombing; Ade Marsinta Arsani; Ni Komang Semara Yanti; Putu Pande Wahyu Diatmika (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2023)
This study aims to determine factors influencing a person's smoking status. The independent variables used were gender, working status, marital status, age, and average length of schooling. The data comes from the 2014 Indonesian Family Life Surveys (IFLS). The analytical method used is binomial/binary logistic regression. The results showed that all of the independent variables significantly affected a person's decision to smoke. Partially, age, working status, marital status, and gender positively affect a person's decision to smoke. This result means that at a higher age, a working, married and male person has a greater chance to smoke than a younger, single/not married, and female. On the other hand, the average length of schooling significantly negatively affects smoking, meaning that the higher the education, the lower the chance of smoking. Therefore, regulations that are right on target, both by the government and society, are needed to reduce the number of smokers in Indonesia